Patterns of partial edentulism based on Kennedy’s classification among patients reporting to Nepal Medical College and Teaching Hospital - Rana, Samskar Bickram; Acharya, Binod; Bhochhibhoya, Amar; Sharma, Rinu; Acharya, Jemish; Mainali, Apekshya (Journal of Kathmandu Medical College, 2018)
Background: Edentulism is a sequel of tooth loss which leads to impairment of normal function, comfort, aesthetics and speech. It also leads to various undesirable consequences like occlusal discrepancies, migration and spacing of surrounding teeth, supra eruption, loss of space, temporomandibular disorders and other unwanted changes. Little is known about the prevalence of patterns of edentulism in Nepal.Objectives: To assess the prevalence of Kennedy’s classification on partially edentulous patients.Methodology: A prospective cross-sectional study was carried out among 300 patients within the age of 18-80 years visiting the Department of Oral Medicine and Radiology, College of Dental Science and Hospital -Nepal Medical College  with at least one missing tooth from Jan 2018-March 2018.Results: Out of 300 patients enrolled, a majority were female (178; 59.3%). The patients mostly affected by partially edentulous condition were among the age group of 51 to 60 years (78; 26%). The distribution of partially edentulous areas were similar in maxillary (80; 26%) and mandibular (85; 28.3%) arches and 45% of the patients (n=135) had one or more missing tooth/teeth on both arches. Kennedy’s class III was found in more than 31% of the patients (n=94) in the maxillary arch and 30% (n=91) in the mandibular arch. Likewise, Kennedy’s class III with modification 1 was seen in 21% (n=62) cases in the maxillary and 24% (n=72) cases in the mandibular arch.Conclusion: Kennedy’s class III and Kennedy’s class III with modification 1 were the most common type of pattern of partially edentulous area on both arches.